Effects of Inducible Nitric Oxide Synthase Inhibition on Cardiovascular Risk of Adult Endotoxemic Female Rats: Role of Estrogen - Castardo-de-Paula, Jaqueline C.; de Campos, Blenda H.; de Jager, Lorena; Amorim, Eric D. T.; Zanluqui, Nágela G.; de Farias, Carine C.; Higachi, Luciana; Pinge-Filho, Phileno; Barbosa, Décio S.; Martins-Pinge, Marli C. (Frontiers in Physiology, 2018)
Aim: Autonomic modulation responds to ovarian hormones and estrogen increases nitric oxide bioavailability. Also, females have minor susceptibility to sepsis and a higher survival rate. However, few studies have evaluated the role of estrogen in cardiovascular, autonomic and oxidative parameters during initial endotoxemia and under inducible nitric oxide synthase (iNOS) inhibition in female rats. Methods: Female wistar rats were subjected to ovariectomy and divided into 3 groups: OVX (ovariectomized), OVX+E (OVX plus daily estradiol) and SHAM (false surgery). After 8 weeks, mean arterial pressure (MAP) and heart rate (HR) were recorded in non-anesthetized catheterized rats, before and after intravenous LPS injection, preceded by S-methylisothiourea sulphate (SMT) injection, or sterile saline. Cardiovascular recordings underwent spectral analysis for evaluation of autonomic modulation. 2 hours after LPS, plasma was collected to assess total radical-trapping antioxidant (TRAP), nitrite levels (NO2), lipoperoxidation (LOOH) and paraoxonase 1 (PON1) activity. Results: 2 hours after LPS, females treated with SMT presented a decrease of MAP, when compared to saline-LPS groups. At this same time, all SMT+LPS groups presented an increase of sympathetic and a decrease of parasympathetic modulation of HR. 2 hours after saline+LPS, OVX presented decreased total radical-trapping antioxidant (TRAP) compared to SHAM. When treated with SMT+LPS, OVX did not altered TRAP, while estradiol reduced LOOH levels. Conclusion: iNOS would be responsible for sympathetic inhibition and consumption of antioxidant reserves of females during endotoxemia, since iNOS is inhibited, treatment with estradiol could be protective in inflammatory challenges.